Nucleocytoplasmic Relations in a Mutator-Suppressor System of DROSOPHILA ANANASSAE - Hinton, Claude W. (1981)
A partially characterized mutator-suppressor system, previously identified in the ca; stw stock of Drosophila ananassae, was shown to exist in the ca ancestral stock; it consists of a clastogenic mutator of sperm chromosomes and a supressor that functions in the oöcyte soon after fertilization. Transmission of these components was monitored by Minute mutation frequencies produced by the progeny of recurrently backcrossed hybrid females derived from reciprocal outcrosses of the ca stock. In this way, the mutator was shown to be an extrachromosomally transmitted element whose propagation depends upon nuclear genes. Suppressivity was found to be determined by nuclear genes, some of which are expressed only after a delay of several generations. Neither the mutator nor its suppressor appear to be infectious. Measurement of dominant lethal frequencies showed that the suppressor is completely effective in repair of premutational lesions induced by the mutator. The properties of this mutator-suppressor system were compared with those of hybrid dysgenesis in Drosophila melanogaster.